IoT based facial recognition door access control home security system using raspberry pi - Syafeeza Ahmad Radzi; M.K. Mohd Fitri Alif; Y. Nursyifaa Athirah; A. S. Jaafar; A. H. Norihan; M. S. Saleha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The home security system has become vital for every house. Previously, most doors can be open by using traditional ways, such as keys, security cards, password or pattern. However, incidents such as a key loss has led to much worrying cases such as robbery and identity fraud. This has become a significant issue. To overcome this problem, face recognition using deep learning technique was introduced and Internet of Thing (IoT) also been used to perform efficient door access control system. Raspberry Pi is a programmable small computer board and used as the main controller for face recognition, youth system and locking system. The camera is used to capture images of the person in front of the door. IoT system enables the user to control the door access.